Depletion of follicular B cell-derived antibody secreting cells does not attenuate angiotensin II-induced hypertension or vascular compliance - Figueiredo Galvao, Hericka Bruna; Lieu, Maggie; Moodley, Seyuri; Diep, Henry; Jelinic, Maria; Bobik, Alexander; Sobey, Christopher G.; Drummond, Grant R.; Vinh, Antony (Frontiers in Cardiovascular Medicine, 2024)
Introduction: Marginal zone and follicular B cells are known to contribute to the development of angiotensin II-induced hypertension in mice, but the effector function(s) mediating this effect (e.g., antigen presentation, antibody secretion and/or cytokine production) are unknown. B cell differentiation into antibody secreting cells (ASCs) requires the transcription factor Blimp-1. Here, we studied mice with a Blimp-1 deficiency in follicular B cells to evaluate whether antibody secretion underlies the pro-hypertensive action of B cells. Methods: 10-to 14-week-old male follicular B cell Blimp-1 knockout (FoB-Blimp-1-KO) and floxed control mice were subcutaneously infused with angiotensin II (0.7 mg/kg/d) or vehicle (0.1% acetic acid in saline) for 28 days. BP was measured by tail-cuff plethysmography or radiotelemetry. Pulse wave velocity was measured by ultrasound. Aortic collagen was quantified by Masson's trichrome staining. Cell types and serum antibodies were quantified by flow cytometry and a bead-based multiplex assay, respectively. Results: In control mice, angiotensin II modestly increased serum IgG3 levels and markedly increased BP, cardiac hypertrophy, aortic stiffening and fibrosis. FoB-Blimp-1-KO mice exhibited impaired IgG1, IgG2a and IgG3 production despite having comparable numbers of B cells and ASCs to control mice. Nevertheless, FoB-Blimp-1-KO mice still developed hypertension, cardiac hypertrophy, aortic stiffening and fibrosis following angiotensin II infusion. Conclusions: Inhibition of follicular B cell differentiation into ASCs did not protect against angiotensin II-induced hypertension or vascular compliance. Follicular B cell functions independent of their differentiation into ASCs and ability to produce high-affinity antibodies, or other B cell subtypes, are likely to be involved in angiotensin II-induced hypertension. 1 Deleted: The present study sought to determine the importance of 112 IgG antibody production to the pro-hypertensive functions of B cells.